OTSSP167 leads to follicular dysplasia and negatively affects oocyte quality in mice. (30th June 2022) - Zhang, Xin-Ran; Ouyang, Ying-Chun; Meng, Tie-Gang; Zhang, Hong-Yong; Yue, Wei; Yan, Feng-Ze; Xue, Yue; Schatten, Heide; Wang, Zhen-Bo; Sun, Qing-Yuan
Abstract: OTSSP167 is an anti-tumor drug significantly inhibiting tumor growth in xenotransplantation studies using mouse breast, lung, prostate, and pancreatic cancer cell lines. Its phase I clinical trial has been completed, indicating its great potential for future treatment of solid tumors. However, its drug-related adverse effects on reproductive systems have not yet been reported. In this study, we evaluated the effects of OTSSP167 on reproduction of female mice by determining oocyte quality and follicular development. We selected four-week-old female ICR mice for a 21-day intraperitoneal injection of OTSSP167 at a dose of 5 mg/kg/d. We found that OTSSP167 could block the meiotic process of oocytes, leading to a decrease in oocyte maturation and ovulated oocyte numbers, as well as a decrease in the quality of oocytes. The results showed that OTSSP167 treatment caused disordered spindle assembly, decreased mitochondria membrane potential, and increased accumulation of reactive oxygen species in oocytes. Further investigation showed that OTSSP167 induced DNA double-strand breaks, as indicated by increased levels of γH2AX in oocytes of primordial follicles and granulosa cells of growing follicles, which induced follicular atresia and decreased the numbers of follicles at various growing stages. Our study suggests that OTSSP167 treatment may have serious effects on the ovary and consequences for female cancer patients, providing strong evidence for the necessity of protecting female fertility in clinical OTSSP167 trials.